The Development of Problem Based Learning Canva-Assisted Teaching Materials to Improve Mathematical Probem Solving Ability on Integer - Fifiana, Qistina; Bernard, Martin; Yuliani, Anik (IKIP Siliwangi, 2024)
This study aims to define the process of developing educational materials in the form of workbooks for students across the entire document using a Canva-supported problem-based learning approach to determine the feasibility of educational materials developed, determine the effectiveness of the educational materials developed, and identify limitations. encountered by researchers during development. instructional materials, collect data on teaching materials, learning objectives to be achieved, and media used by students to date. The study also asked for information on whether school facilities support the learning process. The type of research used is research and development (R&D) with a 4D development model (Define, Design, Develop, Dissemination). The selected study site was MT Nurul Hidayah Batujajar. Due to the evolution of the educational material, especially in limited testing, the correct result is 89% with the most likely interprnal material is 83% with the interpretations very realistic and in extensive testing the confirmatory result is 91% with most likely interpretations, the actual result of the teaching material 86% with very realistic interpretations. The results of this study show that the process of developing teaching aids is well conducted. This study can be used as a reference for further studies as this study meets the very feasibility criteria.